Historical borders and maps as symbolic supports to master narratives and history education. (October 2021) - Parellada, Cristian; Carretero, Mario; Rodríguez-Moneo, María
This article represents an attempt to establish a fruitful dialogue among the field of border studies, history education, sociocultural psychology, and the history of cartography. Seminal studies on borders have asserted that the historical maps included in textbooks are basically an imagined representation. This paper will consider the extent to which cultural and educational origins and uses of these maps, particularly in school settings, act as a support to historical essentialist views. Via the example of history education in Argentina, we carried out an empirical and theoretical examination of the processes of cultural production and consumption of historical maps and their relationship to historical master narratives. Results show that most laypeople largely think of national borders as possessing an essential and immutable character. We consider that closer study, from a sociocultural perspective, of the relationship between master narratives and historical maps may add an enriching element to the existing body of work produced by border studies.